Effects of voltage sags on industrial processes: Case study - Almeida, Danilo Rodrigues [UNESP]; Cebrian, Juan Carlos [UNESP] (My University, 2021)
A voltage dip (or sag) is a sudden reduction in the supply voltage on one or more phases to a value between 90% and 1% of the reference voltage followed by a voltage recovery shortly afterward. In recent years, interruptions, or failures in manufacturing processes due to the poor quality of energy supplied have attracted the interest of industrial consumers, mainly because these events represent significant financial losses to the industrial sector. The failure of some equipment can lead to a partial or total shutdown of the production chain. In this context, this paper shows a study of the case of a supervisory system that can estimate the process immunity time (PIT) of a machine. The estimation process considers PIT values of each equipment that participates in the operational control of the machine, their supportability curves to voltage sags, and their respective connections (serial, parallel, etc.). The results show that the supervisory system is a useful tool to assist planners during decision-making to reduce operating costs.
Keywords: Industrial Processes; Industry 4.0; Voltage sags